2006
DOI: 10.1523/jneurosci.4080-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity of the Hypothalamic–Pituitary–Adrenal Axis Early in Life Requires Recurrent Recruitment of Stress-Regulating Brain Regions

Abstract: An eloquent example of experience-induced neuroplasticity involves the enduring effects of daily "handling" of rat pups on the expression of genes regulating hormonal and behavioral responses to stress. Handling-evoked augmentation of maternal care of pups induces long-lasting reduction of hypothalamic corticotropin releasing hormone (CRH) expression and upregulates hippocampal glucocorticoid receptor levels. These changes promote a lifelong attenuation of hormonal stress responses. We have found previously th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
154
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(166 citation statements)
references
References 75 publications
(71 reference statements)
10
154
0
2
Order By: Relevance
“…Indeed, a general divergence of pCREB and Fos expression in response to sensory stimulation ('experience') in the immature rodent has recently been described. 82 At both ages, blocking CRH receptors within the hippocampus, and without interference with systemic glucocorticoid release, abrogated the ability of the 'psychological' stress to activate hippocampal neurons. This, supported by the fact that many of the activated neurons in the hippocampal formation expressed the CRF 1 receptor, points to a substantial role of CRH receptor activation in the transduction of stress signals within the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a general divergence of pCREB and Fos expression in response to sensory stimulation ('experience') in the immature rodent has recently been described. 82 At both ages, blocking CRH receptors within the hippocampus, and without interference with systemic glucocorticoid release, abrogated the ability of the 'psychological' stress to activate hippocampal neurons. This, supported by the fact that many of the activated neurons in the hippocampal formation expressed the CRF 1 receptor, points to a substantial role of CRH receptor activation in the transduction of stress signals within the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal separation during postnatal life in mice or rats for instance, can increase stress reactivity, induce behavioural despair and alter cognitive functions in some models 1,7,8,[33][34][35][36] but can have opposite effects in other models 37,38 . Although paradoxical at first sight, these findings indicate that the impact of early stress can vary, probably due to differences in experimental paradigms or in the sensitivity of the models.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Avishai-Eliner and collaborators have shown that the permanent down-regulation of hypothalamic CRH-mRNA levels observed in rats handled daily from postnatal days 3 to 14 was evident by postnatal day 9 and was sustained through postnatal days 23 and 45, i.e., beyond puberty (Avishai-Eliner et al, 2001;Fenoglio et al, 2006). These animals exhibit a behavioral profile of decreased anxiety and HPA responses in adulthood.…”
Section: Discussionmentioning
confidence: 99%